Recovery of Bearings and Distances for Internal Lots From Cadastral Perimeter Survey Data: Case Studies in Several States of Peninsular Malaysia - A. Kadir, Abd. Majid; Ses, Shahrum; Teng, Chee Boo; Tan, Seng Huat (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1998)
A study is being carried out to investigate the most appropriate way of determining the missing bearings and distances for internal cadastral lots where the boundary lines are mainly represented on the certified plans (CPs) by scaled distances only. A computer program has been written to compute the bearing and distance for the related lines using the perimeter of the lots which were defined by second class surveys. The computed bearings and distances were later used to re-compute the area of the internal lots and compared with areas given by the certified plans. Results from test computations which has been carried out in selected areas in several states of Peninsular Malaysia indicate that the average differences between the computed and certified areas for the internal lots is less than 1%. Further efforts are being made so that the differences could be well distributed and mirlimized within the area specified by the perimeters.